Metode Terjemah Diterapkan untuk Meningkatkan Pemahaman Siswa terhadap Kandungan Ayat Al-Qur’an dan Hadis - Yanto Maulana Restu; Mirna Rahmawati; Nasarudin Nasarudin; Silmi Hauzan; Aqil Hidayatullah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe the implementation of a translation-based learning strategy for Al-Qur’an and Hadith in improving students’ comprehension at MTs Mu’min Ma’sum. The background of this research stems from the issue that learning activities are still primarily focused on memorization, causing students to struggle with understanding the meaning of Qur’anic verses and hadiths in depth. The translation strategy was selected because it enables students to recognize the meaning of vocabulary, sentence structure, and the contextual messages contained within, thereby making the learning process more meaningful. This study employs a descriptive qualitative method using observation, interviews, documentation, and data triangulation to ensure the validity of the findings. The implementation of the strategy includes word analysis, understanding the context of verses, group discussions, noting essential meanings, and summarizing lesson content. The results show that the translation strategy enhances students’ active engagement in the learning process, strengthens their ability to explain verse meanings, and helps them connect the messages of the Qur’an and Hadith with their daily learning experiences. Although some students still require assistance during the adaptation period of the Merdeka Curriculum, overall, this strategy is considered relevant, flexible, and effective in improving students’ comprehension and the quality of Al-Qur’an and Hadith learning in the madrasah. Keywords: Translation-Based Learning, Al-Qur’an and Hadith, Student Comprehension, Constructivism, Merdeka Curriculum